Review of Molavi’s fables in Divan-I Shams - چنور برهانی (تاریخ ادبیات, 2014)
Narrative allegory is a story with two meanings: a preliminary meaning and secondary meaning that lies beneath the surface layer. Fable is a type of allegory, and consists of a short story which is intended to convey a moral lesson. In Fable, characters are often animals. But inanimate objects, humans and gods may also appear in it. Fable has also been used in Persian mystical parables to express the concepts of theoretical mysticism and the instructions of practical mysticism. One of the artistic aspects of Rumi's work in Divan-I Shams is the use of narrative allegories. There are 14 fables among these narrative allegations. There are two types of fables in terms of processing methodology: 1. Fables with fictional action (6), 2. fables in the form of a conversation or stage story (8). In both categories, the plot and action of the story is very simple and primitive. All fables contains two characters and two to seven actions. The narrator in mostly omniscient and the point of view is external. The tone of most fables is satirical. 4 of his fables are moral-mystical allegory and 10 of his fables are Thought allegory. In the thought allegories , Rumi has described the theoretical mysticism, the Quranic concept of kindness and the theological concept of acquisition.